COMPETITIVENESS OF TRANSPORT INDUSTRY ENTERPRISES IN THE CONDITIONS OF DIGITAL TRANSFORMATION AND EUROPEAN UNION POLICIES - SPITSYNA Anhelinа; GALYTSKYI, Bogdan; LAVRIK, Halyna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the study of modern aspects of competitiveness management of transport enterprises in the context of digital transformation and the requirements of the European Union’s integration policy. The concept of competitiveness is generalized as a multidimensional category that reflects not only the ability of an enterprise to withstand market competition but also its potential for long-term sustainable development. Particular attention is paid to the hierarchy of factors shaping competitiveness, including production and financial resources, intellectual and labor capabilities, managerial competencies, innovative potential, and the ability to adapt to external changes. The necessity of creating an effective system of competitiveness management at enterprises is substantiated, especially under conditions of growing global competition and rapid digitalization. Such a system should be based on the balanced use of production efficiency, financial stability, workforce qualifications, and innovation-driven strategies. The study highlights the challenges faced by Ukrainian transport enterprises, such as the globalization of markets, the impact of technological progress, and the urgent need to comply with sustainable development standards and EU regulations. The research emphasizes that the integration of advanced digital tools—big data analytics, SaaS solutions, business process automation, and artificial intelligence (AI)—is a decisive factor in enhancing efficiency, optimizing resource use, and strengthening market positioning. It is established that the intensification of competition in the global transportation market and Ukraine’s integration into European and international transport systems require fundamentally new approaches to sectoral development and competitiveness growth. The integration of digital solutions with sustainable development practices stands out as a critical condition for ensuring resilience, customer trust, and innovative growth. Digital transformation not only enables enterprises to optimize operations and reduce transaction costs but also provides opportunities for predictive analytics, smart logistics, and more environmentally friendly business models. The study concludes that the systematic implementation of digital technologies allows transport enterprises to maintain stability in turbulent market conditions, increase customer loyalty, expand market share, and ultimately form sustainable competitive advantages in the dynamic global economy.